Metagenomic Analysis Suggests Modern Freshwater Microbialites Harbor a Distinct Core Microbial Community - White, Richard Allen; Chan, Amy M.; Gavelis, Gregory S.; Leander, Brian S.; Brady, Allyson L.; Slater, Gregory F.; Lim, Darlene S. S.; Suttle, Curtis A. (Frontiers in Microbiology, 2016)
Modern microbialites are complex microbial communities that interface with abiotic factors to form carbonate-rich organosedimentary structures whose ancestors provide the earliest evidence of life. Past studies primarily on marine microbialites have inventoried diverse taxa and metabolic pathways, but it is unclear which of these are members of the microbialite community and which are introduced from adjacent environments. Here we control for these factors by sampling the surrounding water and nearby sediment, in addition to the microbialites and use a metagenomics approach to interrogate the microbial community. Our findings suggest that the Pavilion Lake microbialite community profile, metabolic potential and pathway distributions are distinct from those in the neighboring sediments and water. Based on RefSeq classification, members of the Proteobacteria (e.g alpha and delta classes) were the dominant taxa in the microbialites, and possessed novel functional guilds associated with the metabolism of heavy metals, antibiotic resistance, primary alcohol biosynthesis and urea metabolism; the latter may help drive biomineralization. Urea metabolism within Pavilion Lake microbialites is a feature not previously associated in other microbialites. The microbialite communities were also significantly enriched for cyanobacteria and acidobacteria, which likely play an important role in biomineralization. Additional findings suggest that Pavilion Lake microbialites are under viral selection as genes associated with viral infection (e.g CRISPR-Cas, phage shock and phage excision) are abundant within the microbialite metagenomes. The morphology of Pavilion Lake microbialites changes dramatically with depth; yet, metagenomic data did not vary significantly by morphology or depth, indicating that microbialite morphology is altered by other factors, perhaps transcriptional differences or abiotic conditions. This work provides a comprehensive metagenomic perspective of the interactions and differences between microbialites and their surrounding environment, and reveals the distinct nature of these complex communities.